Behavioral strategies for reducing disease transmission in the workplace. Issue 4 (16th October 2020) - Gravina, Nicole; Nastasi, Jessica A.; Sleiman, Andressa A.; Matey, Nicholas; Simmons, Davis E.
Abstract : The coronavirus pandemic highlighted that workplaces may serve as a hub of disease transmission if proper precautions are not enacted. The Centers for Disease Control recommends several strategies for decreasing the spread of illnesses in the workplace, including a) promoting proper hand hygiene, b) cleaning and sanitizing the work area, c) encouraging sick employees to stay home, d) personal protective equipment, and, e) social distancing. Research suggests that instructions are often not sufficient to change work behaviors, and behavioral interventions may be needed. Thus, the present paper reviews existing research that informs the implementation of behavioral strategies to reduce the spread of disease in the workplace, and makes recommendations for organizations to protect employees, clients, and customers. Intervention components such as training, prompts, the reduction of response effort, clear workplace policies, feedback, and consequences are discussed, and practical recommendations and suggestions for future research are provided.